Challenges of Growth and Globalization in the Middle East and North Africa - Davoodi, Hamid Reza (International Monetary Fund, 2003)
The Middle East and North Africa (MENA) is an economically diverse region. Despite undertaking economic reforms in many countries, and having considerable success in avoiding crises and achieving macroeconomic stability, the region's economic performance in the past 30 years has been below potential. This paper takes stock of the region's relatively weak performance, explores the reasons for this out come, and proposes an agenda for urgent reforms